2021
DOI: 10.1111/and.14036
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of n‐acetyl cysteine on gibberellic acid‐induced testicular dysfunction through regulation of inflammatory cytokines, steroid and antioxidant activity

Abstract: In agriculture, gibberellic acid (GA3) is commonly used with extreme dangers for public health. The current research evaluates the improving effects of n‐acetyl cysteine (NAC, 150 mg/kg bw) co‐administered with GA3 (55 mg/kg bw) mediated testicular injury. Twenty‐four male albino rats were split into 4 groups: Negative control (CNT), NAC group, positive GA3 group and protective group, co‐administered NAC plus GA3. On day 21, rats were anesthetised then euthanised by decapitation. Blood samples were collected; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…Our data are in agreement with those of other studies (Soliman et al, 2021b) that revealed a decrease in the activity of antioxidants in adult rats (Khalaf et al, 2019). GSH and SOD are oxidative stress biomarkers that are required for testes integrity (H. Yang et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data are in agreement with those of other studies (Soliman et al, 2021b) that revealed a decrease in the activity of antioxidants in adult rats (Khalaf et al, 2019). GSH and SOD are oxidative stress biomarkers that are required for testes integrity (H. Yang et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…In the testes of rats, GA3 has been reported to cause DNA damage and oxidative stress (Sayed et al, 2020;Soliman et al, 2009;Soliman et al, 2021a;Soliman et al, 2021b). The use of GA3 for an extended period of time reduced antioxidant enzyme activity and elevated oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…QR possesses both direct and indirect antioxidant mechanisms(Costa et al, 2016). Our data are consistent with those ofSoliman et al (2021), confirming overexpression of inflammatory cytokines (TNFα, IL-1β), reduced expression of anti-inflammatory cytokine IL-10 in GA3-treated rats, and increased mRNA expression of NF-κB. All were normalized in the group cotreated with QR +GA3.…”
supporting
confidence: 86%
“…The control group (CNT) received saline; the quercetin group (QR) received 50 mg/kg/BW quercetin dissolved in saline via daily intraperitoneal (i.p.) injection for 4 weeks (Al-Otaibi et al, 2018;Bo et al, 2018); the gibberellic acid group (GA3) received 55 mg/kg/ BW GA3 via daily oral gavage for 4 weeks (Lafi et al, 2018;Soliman et al, 2021); and the protective group (QR +GA3) was maintained under experimental settings (Alsemeh et al, 2019a(Alsemeh et al, , 2019b, injected with QR and gavaged with GA3 at the same doses as those used in the QR and GA3 groups. Quercetin was injected an hour before GA3 administration to confirm its protective effects.…”
Section: Animal Handling and Experimental Designmentioning
confidence: 99%